Aesthetics and Education in Imam Al-Shafi'i's "The Honor of Knowledge": An Analysis of Prosody, Rhyme, and Educational Values: الجماليات والتربية في شعر "شرف العلم" للإمام الشافعي: تحليل االعروض والقافية والقيم التعليمية - Nida Fauziyah Fitriani; Minatur Rokhim (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
Poetry has played a central role in Arab civilization since the pre-Islamic era, functioning not only as a form of artistic expression but also as a medium of education. Within Arabic poetry, the sciences of ‘Arūḍ and Qāfiyah constitute fundamental structural elements, although they are often regarded as complex and difficult to master. This study proposes an integrated analytical approach that combines the structural analysis of classical Arabic poetry with moral education by examining the poem Syarfu al-‘Ilmu by Imam Syafi‘i. Using a descriptive qualitative method with an analytical approach grounded in Ahmad Hasan al-Zayyat’s conception of poetry, this research analyzes the poem’s prosodic and rhyming structures alongside its educational values. The findings reveal that the poem employs the kāmil meter with the mutafā‘ilun pattern, which undergoes permissible variations through ziḥāf and ‘illah, as well as a qāfiyah muṭlaqah mujarradah with the letter sīn as rawī. Beyond its formal structure, the poem conveys core scholarly values, including proper conduct (adab), diligence, and perseverance in the pursuit of knowledge. This study demonstrates that the aesthetic value of Arabic poetry lies not only in its sonic harmony but also in the depth of its moral message. By integrating prosodic analysis with ethical interpretation, this research contributes to Arabic literary studies and offers pedagogical insights for developing more accessible and value-oriented approaches to teaching classical Arabic poetry in contemporary educational contexts. لعب الشعر دورًا محوريًا في الحضارة العربية منذ العصر الجاهلي، إذ لم يقتصر دوره على كونه شكلًا من أشكال التعبير الفني فحسب، بل تعداه إلى كونه وسيلةً للتعليم. وفي الشعر العربي، تُشكل علوم العروض والقافية عناصرَ أساسيةً في بنيته، على الرغم من أنها تُعتبر في كثير من الأحيان معقدةً وصعبة الإتقان. تقترح هذه الدراسة منهجًا تحليليًا متكاملًا يجمع بين التحليل البنيوي للشعر العربي الكلاسيكي والتربية الأخلاقية، وذلك من خلال دراسة قصيدة "شرح العلم" للإمام الشافعي. وباستخدام منهج وصفي نوعي، مع منهج تحليلي قائم على مفهوم أحمد حسن الزيات للشعر، يُحلل هذا البحث البنية العروضية والقافية للقصيدة، إلى جانب قيمها التربوية. تكشف النتائج أن القصيدة تستخدم الوزن الكامل بنمط التفائلون، الذي يخضع لتغيرات جائزة عبر الزحاف والإلاه، بالإضافة إلى وزن قافية مطلقة مجرّدة بحرف السين رويه. وإلى جانب بنيتها الشكلية، تنقل القصيدة قيماً علمية جوهرية، منها حسن السلوك والاجتهاد والمثابرة في طلب العلم. وتُبين هذه الدراسة أن القيمة الجمالية للشعر العربي لا تكمن فقط في تناغمه الصوتي، بل أيضاً في عمق رسالته الأخلاقية. ومن خلال دمج التحليل العروضي مع التفسير الأخلاقي، يُسهم هذا البحث في الدراسات الأدبية العربية، ويُقدم رؤى تربوية لتطوير مناهج أكثر سهولة وقيمة لتدريس الشعر العربي الكلاسيكي في السياقات التعليمية المعاصرة.